English English - Safitri, Dwi; Inayah, Nailil; Taufik, Taufik; Astuti, Julia (JPPS (Jurnal Penelitian Pendidikan Sains), 2024)
Objective: The aim of this investigation is to study and describe a Problem-Based Learning (PBL) model based on local wisdom assisted by interactive magazines to enhance students' critical thinking skills. Method: This study used a quasi-experimental design with a saturated sample technique. The tools employed were observation sheets monitoring both teacher and student activities, critical thinking tests, and a questionnaire. Results: Based on observations results, it was found that teacher and student activities were very good with percentages of 96,64% and 91,96% respectively. According to the t-test, the significance (two-tailed) value was 0.000, which is less than 0.05, leading to the rejection of the null hypothesis (H0). Therefore, it can be inferred that students' critical thinking skills differ significantly between the experimental and control classes. The category of critical thinking skills was less initially and improved into a critical category after the implementation of local wisdom-oriented problem-based learning assisted by an interactive e-magazine. Moreover, Learning using interactive magazines was also interesting, effective, and practical for students. Novelty: This research specifies the problem given to material or issues related to local wisdom of Malaysia for Indonesian students. Besides, the implementation of the model is assisted by the interactive media to strengthen the effects.